Ellis–van Creveld syndrome associated with chronic intestinal pseudo‐obstruction. Issue 1 (28th January 2016) - Iwakura, Hideo; Fujii, Katsunori; Furutani, Yoshiyuki; Takatani, Tomozumi; Ebata, Ryota; Nakanishi, Toshio; Mitsunaga, Tetsuya; Saito, Takeshi; Kishimoto, Takashi; Yoshida, Hideo; Shimojo, Naoki
Abstract: Ellis–van Creveld (EVC) syndrome is a rare autosomal recessive disorder characterized by hypoplastic nails, polydactyly, and achondroplasia. Patients usually exhibit normal cognitive function and no remarkable developmental delay. We herein present an unusual case of EVC syndrome. A Japanese 2‐year‐old boy was born at term, but immediately developed severe respiratory failure due to thorax deformity, postaxial polydactyly and nail hypoplasia. We identified a novel pattern of germinal compound heterozygous nonsense EVC2 mutations of c.1814C > A (p. S605X) and c.2653C > T (p. R885X), leading to the diagnosis of EVC syndrome. Interestingly, he also had severe developmental delay, and suddenly developed excessive abdominal distension at the age of 2. On surgery, extensive necrotic bowel with chronic intestinal pseudo‐obstruction was noted. This is, to our knowledge, a most severe phenotype of EVC syndrome, illustrating that the specific pattern of EVC2 compound heterozygous mutations may cause severe developmental delay and intestinal malfunction.